2022
DOI: 10.1172/jci.insight.153584
|View full text |Cite
|
Sign up to set email alerts
|

NR1D1 controls skeletal muscle calcium homeostasis through myoregulin repression

Abstract: The sarcoplasmic reticulum (SR) plays an important role in calcium homeostasis. SR calcium mishandling is described in pathological conditions such as myopathies. Here, we investigated whether the nuclear receptor subfamily 1 group D member (NR1D1, also called REV-ERBα) regulates skeletal muscle SR calcium homeostasis. Our data demonstrate that NR1D1 deficiency in mice impairs SERCA-dependent SR calcium uptake. NR1D1 acts on calcium homeostasis by repressing the SERCA inhibitor myoregulin through direct bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…147 Extensive research since has further revealed the regulatory roles of REV-ERBs in skeletal muscle function. 86,149,150 For example, REV-ERBβ has been implicated in skeletal muscle lipid metabolism since ectopic expression of its dominant-negative form upregulated expression of genes associated with fatty acid uptake in skeletal muscle. 151 Consistently, SR8278, an antagonist of REV-ERBs, was found to activate expression of myogenesis genes including Myogenic determination 1 (Myod), Myogenin (Myog), and Major histocompatibility complex 3 (Mhc3), suggesting a role of REV-ERBs in myogenesis.…”
Section: Muscle Pathologiesmentioning
confidence: 99%
“…147 Extensive research since has further revealed the regulatory roles of REV-ERBs in skeletal muscle function. 86,149,150 For example, REV-ERBβ has been implicated in skeletal muscle lipid metabolism since ectopic expression of its dominant-negative form upregulated expression of genes associated with fatty acid uptake in skeletal muscle. 151 Consistently, SR8278, an antagonist of REV-ERBs, was found to activate expression of myogenesis genes including Myogenic determination 1 (Myod), Myogenin (Myog), and Major histocompatibility complex 3 (Mhc3), suggesting a role of REV-ERBs in myogenesis.…”
Section: Muscle Pathologiesmentioning
confidence: 99%
“…These disturbances may perturb the expression of circadian clock genes [ 37 ]. Notably, clock genes capture our interest as they orchestrate immune function, energy metabolism, and mitophagy [ 25 , 38 , 39 ], thus exerting diverse impacts on mammalian physiology. However, the mechanisms by which the circadian clock affects UC remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“… 146 Extensive research since has further revealed the regulatory roles of REV-ERBs in skeletal muscle function. 84 , 148 , 149 For example, REV-ERBβ has been implicated in skeletal muscle lipid metabolism since ectopic expression of its dominant-negative form upregulated expression of genes associated with fatty acid uptake in skeletal muscle. 150 Consistently, SR8278, an antagonist of REV-ERBs, was found to activate expression of myogenesis genes including Myogenic determination 1 ( Myod ), Myogenin ( Myog ), and Major histocompatibility complex 3 ( Mhc3 ), suggesting a role of REV-ERBs in myogenesis.…”
Section: Therapeutic Relevance Of Rev-erbs and Rorsmentioning
confidence: 99%